In-service EFL Teachers’ Critical Reflective Practice: An Appraisal Analysis - Lulut Widyaningrum; Yan Mujiyanto; Issy Yuliasri; Puji Astuti (Universitas Negeri Semarang, 2022)
This article aims at finding out how the EFL in-service teachers reflect their teaching practice and what can be learned by EFL in-service teachers about reflecting their reflective practice to their teacher professional development. Two in-service teachers at an Indonesian university participated in this study. The data in this study are collected from Narrative questionnaire on critical reflection of classroom practice, and in-depth interview. The qualitative data are the in-service teachers’ critical reflection dealing with their teaching practice. The finding of the research show that the incident was analyzed using Appraisal theory by Martin & White (2005) becomes a reference for finding out what aspects of lecturer competence they want to target. Continuous reflection should be conducted to make better teaching learning process, so that he can get the impact of reflection activities maximally. Thus, it becomes endeavor for teacher professional development.